Oversight mechanisms and service delivery: a case study of municipal public accounts committee oversight of electricity services in Raymond Mhlaba Local Municipality - Mpofu, Sibabalwe (Rhodes University, Faculty of Humanities, Department of Sociology)
South Africa, as a post-apartheid state is still grappling with socio-economic inequalities such as poverty, unemployment, and inequality. Local government is mandated to play a developmental role and has a responsibility to redress these socio-economic inequalities at grassroots level. According to the Constitution of South Africa, the local government sphere is obligated to adopt and practice good governance. Whilst good governance means different things to different people, this study argues that good governance is characterised by transparency and accountability, and the use of public resources in an accountable and sustainable manner in order to ensure the progressive realisation of the needs of the municipal residents. This study explores the relationship between oversight and service delivery by examining the Municipal Public Accounts Committee's oversight of electricity services in Raymond Mhlaba Municipality (herein referred to as RMM) in South Africa's Eastern Cape Province. It makes use of a case-study research design to inform its data collection and analysis. Officials responsible for electricity service provision and councillors responsible for overseeing the performance of electricity services in RMM were interviewed. These interviews were analysed together with a document analysis of RMM, and a review of relevant local government legislation. The research findings indicate that the Municipal Public Accounts Committee (herein referred to as the MPAC) in RMM failed to engage in effective oversight due to (1) a lack of familiarity with the municipality's plans for electricity services, (2) a lack of familiarity with the targets for revenue collection and expenditure management for electricity services, and (3) a lack of rigorous oversight and monitoring of the municipality's spending and implementation of targets set out in its electricity plans. This study, therefore, reflects the realities of non-effective oversight in municipalities in the Eastern Cape and proposes a model which can improve some of the dire oversight practices which are prevalent in rural municipalities such as RMM.
Keywords: Municipal services -- South Africa; Local government -- South Africa; Local service delivery; Public sector; Oversight; Economics Sociological aspects; Government accountability -- South Africa